Mitochondrial Epigenetics Regulating Inflammation in Cancer and Aging - Chatterjee, Debmita; Das, Palamou; Chakrabarti, Oishee (Frontiers in Cell and Developmental Biology, 2022)
Inflammation is a defining factor in disease progression; epigenetic modifications of this first line of defence pathway can affect many physiological and pathological conditions, like aging and tumorigenesis. Inflammageing, one of the hallmarks of aging, represents a chronic, low key but a persistent inflammatory state. Oxidative stress, alterations in mitochondrial DNA (mtDNA) copy number and mis-localized extra-mitochondrial mtDNA are suggested to directly induce various immune response pathways. This could ultimately perturb cellular homeostasis and lead to pathological consequences. Epigenetic remodelling of mtDNA by DNA methylation, post-translational modifications of mtDNA binding proteins and regulation of mitochondrial gene expression by nuclear DNA or mtDNA encoded non-coding RNAs, are suggested to directly correlate with the onset and progression of various types of cancer. Mitochondria are also capable of regulating immune response to various infections and tissue damage by producing pro- or anti-inflammatory signals. This occurs by altering the levels of mitochondrial metabolites and reactive oxygen species (ROS) levels. Since mitochondria are known as the guardians of the inflammatory response, it is plausible that mitochondrial epigenetics might play a pivotal role in inflammation. Hence, this review focuses on the intricate dynamics of epigenetic alterations of inflammation, with emphasis on mitochondria in cancer and aging.